The Importance and Role of Colors in Interiors - Safarova Nasiba Normatovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The significance of color in interior design extends beyond aesthetic appeal, serving as a vital component in shaping the ambiance and functionality of a space. Color influences emotions, perceptions, and behaviors, playing a crucial role in how individuals experience their environment. In residential, commercial, and public interiors, the strategic application of color can enhance mood, promote productivity, and even affect the perceived size of a room. For instance, warmer tones tend to evoke feelings of comfort and intimacy, while cooler shades can foster a sense of calm and tranquility . Additionally, cultural associations with specific colors further complicate their impact, as these perceptions can vary significantly across different contexts . Therefore, understanding the psychological and emotional implications of color is essential for designers and architects aiming to create spaces that resonate with their intended users . Ultimately, color emerges not merely as an aesthetic choice but as a powerful tool in the art of interior design .